ENHANCING STRESS COPING SKILLS AMONG COLLEGE STUDENTS - Dr. S. Kadhiravan,; K.Kumar, (Researchers World - International Refereed Social Sciences Journal, 2021)
Stress exists in every part of our life. The prevalence of stress is increasing among students in recent years. This is due to various factors such as increased pressure, competition, decreased resources, inadequate family support, exposed to violence through media and increased use of alcohol as well as drugs. The transition from adolescence to adulthood is a difficult journey filled with various risk, rapid changes, and seemingly endless choices. Coping skills can help the youth to navigate through these challenges. These would help students to be self-reliant, solve problems and make informed choices, which in turn promote their physical and psychological well-being. to ascertain the efficacy of a stress coping programme as a means for decreasing perceived stress and increasing the proactive attitude towards stress. This study adopted quasi-experimental design. Forty-four under graduate computer science students were assigned to control group and forty-four students were assigned to experimental group. A training module was developed to promote proactive coping strategies and general self-efficacy and utilized as an experimental intervention. From the result, it is found that the developed training is effective in enhancing proactive coping and general self-efficacy of college students.